2017
DOI: 10.1590/1982-7849rac2017160118
|View full text |Cite
|
Sign up to set email alerts
|

O Efeito da Publicação Científica do Orientador na Publicação dos Seus Orientados

Abstract: Resumo Neste artigo analisamos o efeito da orientação na produção científica dos alunos de doutorado em Administração. A questão essencial de pesquisa é como a competência em produção científica (publicação de artigos) do professor orientador pode influenciar a produção dos orientados doutorados. Por meio de um estudo empírico quantitativo realizado com dados secundários numa base de 313 orientados e 127 professores orientadores de quatro universidades brasileiras, analisamos a relação entre o volume e qualida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
11
0
5
Order By: Relevance
“…Costa et al (2015) highlight that it is up to the advisor to guide the student during their education, as the student's development process is experiential and can occur based on their experiences in the classroom, in their relationship with teachers, course mates, and, especially, with the advisor themself. Falaster et al (2017) argue that there is a relationship between the quality of the guidance and that of the student's academic development. The results of their study indicated that more experienced advisors with higher quality publications influence their students to produce quality publications instead of a high quantity.…”
Section: Feelings and The Advisor-student Relationshipmentioning
confidence: 99%
See 3 more Smart Citations
“…Costa et al (2015) highlight that it is up to the advisor to guide the student during their education, as the student's development process is experiential and can occur based on their experiences in the classroom, in their relationship with teachers, course mates, and, especially, with the advisor themself. Falaster et al (2017) argue that there is a relationship between the quality of the guidance and that of the student's academic development. The results of their study indicated that more experienced advisors with higher quality publications influence their students to produce quality publications instead of a high quantity.…”
Section: Feelings and The Advisor-student Relationshipmentioning
confidence: 99%
“…The attention paid to cognitive aspects instead of affective relationships has been a focus of discussions in the university environment (Veras & Ferreira, 2010). Studies indicate that the relationship between teachers and students have been an influencer of the quality of the activities developed in post-graduation, especially regarding the guidance process for scientific works (Falaster et al, 2017). The advisor performs the role of guide in the student's academic journey; part of the student's success or lack of it can be attributed to their interactions with the advisor, transforming this relationship into a form of partnership in which the final product is the master's dissertation or doctoral thesis (Nóbrega, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Um segundo motivo principal para as coautorias no Brasil seria a orientação. Ao contrário do observado em alguns países, no Brasil o orientador é um dos principais coautores no início da carreira do pesquisador (Falaster et al, 2017). Desta forma, inserindo o pesquisador em redes de pesquisa desde o início do doutorado.…”
Section: Pressões Para Publicar Autoresunclassified